Struktura wielkości prywatnych majątków ziemskich w powiecie sieradzkim przed I wojną światową - Klemantowicz, Dariusz (Biuletyn Szadkowski, 2010)
Before the First World War, Sieradz District was a part of Kalisz Gubernya, and formed the western boundary of Łódź industrial region. Its peripheral location both within the gubernya and in relation to Łódź industrial region, as well as the fact that it was rather late in obtaining rail connections with other parts of the country, consolidated the agricultural character of this district. In 1911 there were 131 private landed estates above 50 ha each. Not all of them were fully owned by their landlords – many were encumbered by debts. According to rough estimates, the landlords formed a group constituting about 0.5% of the district’s population. The majority of the estates (55.7) were medium-sized, with areas between 101–500 ha; 24.4% of the estates were large, from 501 ha to 1000 ha, 13% were small estates up to 100 ha, and only 6.9% had areas between 1000 ha and 2000 ha.